2019
DOI: 10.3390/su11030881
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Intrapreneurial Self-Capital Scale in Malaysian University Students

Abstract: The Intrapreneurial Self-Capital Scale (ISCS) is a 28-item measure intended to measure individual resources used to manage career and life challenges. The Intrapreneurial Self-Capital (ISC) is a higher order construct composed of seven specific constructs: core self-evaluation, hardiness, resilience, creative self-efficacy, decisiveness, goal mastery, and vigilance. In the new research area of the psychology of sustainability and sustainable development, ISC constitutes a promising core of resources to face th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Thus, more efforts should be made to expand the research regarding the mediation effect of ISC on connectedness to nature by recruiting different types of workers from different geographical areas in Italy. Foreign countries should be included in testing such a model in the future as well, since the ISC scale is becoming available in multiple languages [56].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, more efforts should be made to expand the research regarding the mediation effect of ISC on connectedness to nature by recruiting different types of workers from different geographical areas in Italy. Foreign countries should be included in testing such a model in the future as well, since the ISC scale is becoming available in multiple languages [56].…”
Section: Discussionmentioning
confidence: 99%
“…In more recent studies, it showed that intrapreneurial self-capital was significantly associated with flourishing among Spanish employees [28]. Past studies are widely performed in the Western setting, but it is proven that the intrapreneurial self-capital is reliable to be applied among Malaysian youth, especially the undergraduates [29].…”
Section: Intrapreneurial Self-capitalmentioning
confidence: 99%
“…The measurement used in the current study consists of three parts: demographic information, The Intrapreneurial Self-Capital Scale (ISCS) [7] in the Malaysian version [29], the Satisfaction with Life Scale (SWLS) [30], and The Flourishing Scale (FS) [11]. The demographic information includes gender, age, religion, ethnicity and respondents' year of study and academic performance.…”
Section: Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Future research should address this issue by involving workers from different regions of Italy and lines of work. Our results should also be tested in other countries, especially given that the ISC measure is becoming available in multiple languages [24,44]. In this way, cross-cultural invariance of our results could also be tested.…”
Section: Discussionmentioning
confidence: 94%